Communication theory through the ages - Klyukanov, Igor (Routledge, 2019)
Communication Theory Through the Ages presents communication theory as a journey through history by way of asking engaged questions. Encouraging intellectual vitality, the authors show students step by step how theoretical ideas are interconnected and lead to an increasingly complex understanding of communication. Students will be motivated to ask questions as they encounter historical figures, social events, and artifacts, resulting in a richer understanding of the biographical, cultural, and social context for communication theories.